Unsur Fisik Dan Batin Pada Puisi “Aku" "Aku Mencintaimu Diam-Diam" “Rumahku" "Senja Di Pelabuhan Kecil" Karya Chairil Anwar - Dhea Karunia Ramdhini; Reza Rizky Saputra (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Poetry is one of the most interesting and beautiful forms of literary work. The beauty of poetry does not lie solely in the words. The beauty of poetry is also formed by the structure of birth and mind. The structure of birth is the builder of the poem from the outside while the inner structure of the poem is the spirit of a poem so it is very important in a poem itself. The poem "Love and hate" " " My House " " "Senja di Pelabuhan kecil" is one of the literary works by chairil anwar.this research aims to analyze and explain from the inner elements of several poems by chiril anwar the type of research used is library research research the data used is the data written in the form of five poems by chairil anwar